PENGEMBANGAN MEDIA PEMBELAJARAN MATA KULIAH TEKNOLOGI INFORMASI BERBASIS LEARNING MANAGEMENT SYSTEM PADA MAHASISWA PGMI - Juhaeni Juhaeni; Husniyatus Salamah Zainiyati; Safaruddin Safaruddin (STKIP PGRI Situbondo, 2023)
This study aims to 1) develop learning media in information technology courses based on the Learning Management System (LMS); 2) determine the feasibility of learning media for information technology courses based on the Learning Management System (LMS) based on the assessment of material experts, media experts and field trials in information technology courses. This research is a research and development adapted from the ADDIE development model. The research subjects are media experts, material experts for Islamic teacher education students (PGMI) UIN Sunan Ampel Surabaya. The object of research is the development of information technology learning media. Data collection using a questionnaire using a scale of 5. To determine the feasibility of information technology learning media using quantitative descriptive with a percentage Research results 1). Development of information technology learning media based on Learning Management System with Analysis, Design, Development, Implementation and Evaluation (ADDIE); 2). The results of the feasibility test for material experts are in the very feasible category (88%), media experts are in the very feasible category (89%) and field trials are in the very feasible category (85%). Based on the results of the assessment of material experts, media experts and field trials, the LMS-based information technology learning media was declared very feasible (87%) to be used as information technology learning media at the PGMI of UIN Sunan Ampel Surabaya.